Bicuculline and the frog spinal cord - Pixner, D.B. (1974)
1 The effects of bicuculline on dorsal and ventral root activity and upon the depressant effect of γ-aminobutyric acid (GABA) and glycine on ventral root responses have been studied on the isolated spinal cord of the frog. 2 In the absence of stimulation, the alkaloid induced a variety of activity of which the most notable was phasic simultaneous slow wave depolarization in the dorsal and ventral roots which could be reduced or suppressed by magnesium. 3 With low concentrations of bicuculline, the adjacent dorsal root response evoked by a single stimulus was depressed maximally before an increase in the ventral root response could be discerned. 4 The bicuculline-induced dorsal root activity (in the absence of stimulation) was still apparent at times when the evoked dorsal root response was reduced. 5 Bicuculline did not differentiate between the depressant effects of GABA and glycine on the evoked ventral root responses. 6 The excitant effects of bicuculline reported here did not appear to be attributable to specific antagonism of the postsynaptic depressant action of GABA.